Evaluation of Online Progressive Examinations of Infectious Diseases and Clinical Microbiology Specialty Students - Ozturk Kaygusuz, Turkkan; Karabay, Oguz (Bilimsel Tip Yayinevi, 2020)
Introduction: Progressive examinations are required to monitor the development of research assistants in the field of Infectious Diseases and Clinical Microbiology. However, the preparation, conduct and evaluation of these exams also require especial features and experience. In this study, it was aimed to review the experience obtained in the online progressive exams of research assistants conducted by the education commission (EMEK) in the field of IDCM specialization. Materials and Methods: There are two online formative exams per year for research assistants in the IDCM field. In this study, the examinations between 2014-2018 were evaluated. The validity and reliability analyses for each exam were performed, and the difficulty and discrimination indexes of the questions were calculated. Topics with the least correct answers were determined. Results: Over the years, an increase in the number of research assistants was observed. The internal consistency coefficient of the exams was the lowest of the cronbach alpha value of 0.69 and the highest of 0.92. Mean score of the exam was over 69. It was seen that some questions need to be revised in order to be transferred to the question bank. Although clinically rare diseases and basic microbiology questions were answered less frequently, the rate of responding to diseases that are frequently seen in the clinic was higher. Conclusion: In specialist training, online progressive exams facilitate broad-based measurement and evaluation at national level. With the increase of our online exam experience, we can see that there are still aspects that need improvement.
Keywords: Online examination; Expertise students; Progressive exams; Measurement and evaluation